1975
DOI: 10.1128/aac.7.5.530
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by Levorphanol and Related Drugs of Amino Acid Transport by Isolated Membrane Vesicles from Escherichia coli

Abstract: Levorphanol inhibits the transport of the amino acids proline and lysine by cytoplasmic membrane vesicles derived from Escherichia coli. The degree of inhibition increases with increasing levorphanol concentration and ranges from 26% at 10-6 M levorphanol to 92% at 10-3 M levorphanol. The effect is independent of the energy source, since levorphanol inhibits proline uptake to the same extent in the presence of 20 mM D-lactate or 20 mM succinate and in the absence of an exogenous energy source. Levorphanol does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
1979
1979

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In contrast to the effects of levorphanol on RNA synthesis (Simon & VakPraag, 1964a, b), RNA phage replication (Simon, Garwes & Rand, 1970a) and putrescine and amino acid transport (Simon et al, 1970b;Holland & Simon, 1975), which required the presence of the drug and were readily reversed upon its removal, chemotaxis was profoundly inhibited when cells were pretreated and the drug removed prior to testing. Reversal of levorphanol inhibition required at least one generation time in complete growth medium before normal chemotaxis was restored, suggesting the necessity to regenerate a component lost during exposure to the drug.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In contrast to the effects of levorphanol on RNA synthesis (Simon & VakPraag, 1964a, b), RNA phage replication (Simon, Garwes & Rand, 1970a) and putrescine and amino acid transport (Simon et al, 1970b;Holland & Simon, 1975), which required the presence of the drug and were readily reversed upon its removal, chemotaxis was profoundly inhibited when cells were pretreated and the drug removed prior to testing. Reversal of levorphanol inhibition required at least one generation time in complete growth medium before normal chemotaxis was restored, suggesting the necessity to regenerate a component lost during exposure to the drug.…”
Section: Discussionmentioning
confidence: 90%
“…Levorphanol also inhibits the transport of amino acids by intact cells (Simon et al, 1970b) and by isolated cytoplasmic vesicles (Holland & Simon, 1975) of E. coli. These and other studies (Greene & Magasanik, 1967;Gale, 1970a, b;Devinck et al, 1971;Knape, Boquet & Roschethaler, 1972) have suggested that levorphanol and related drugs alter the properties of bacterial cell membranes.…”
Section: Introductionmentioning
confidence: 99%